2023
DOI: 10.1038/s41598-023-34079-x
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of Solanum lycopersicum diseases from temporally-aggregated hyperspectral measurements using machine learning

Abstract: Some plant diseases can significantly reduce harvest, but their early detection in cultivation may prevent those consequential losses. Conventional methods of diagnosing plant diseases are based on visual observation of crops, but the symptoms of various diseases may be similar. It increases the difficulty of this task even for an experienced farmer and requires detailed examination based on invasive methods conducted in laboratory settings by qualified personnel. Therefore, modern agronomy requires the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Their model combined Genetic Algorithms and SVM and achieved overall accuracies (OA) of 90.7% in the distinction of healthy and symptomatic tissues. Tomaszewski et al. (2023) also demonstrated the suitability of hyperspectral measurements and machine learning for the early detection of anthracnose, bacterial speck, early blight, late blight, and septoria leaf, using a temporally-aggregated approach.…”
Section: Discussionmentioning
confidence: 96%
“…Their model combined Genetic Algorithms and SVM and achieved overall accuracies (OA) of 90.7% in the distinction of healthy and symptomatic tissues. Tomaszewski et al. (2023) also demonstrated the suitability of hyperspectral measurements and machine learning for the early detection of anthracnose, bacterial speck, early blight, late blight, and septoria leaf, using a temporally-aggregated approach.…”
Section: Discussionmentioning
confidence: 96%
“…As we move forward from this study, we plan to extend our research to include a wider range of real-world datasets, such as those suggested by Tomaszewski Tomaszewski et al (2023) and Ruszczak Ruszczak and Boguszewska-Mańkowska (2022). Our current focus on a controlled dataset lays the groundwork for this expansion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the indiscriminate spraying of fungicides can lead to unnecessary resource wastage and environmental pollution. Traditional methods of crop disease survey not only consume time and manpower but may also result in mechanical damage to crops [8][9][10]. Consequently, the real-time and efficacious surveillance and mitigation of peanut southern blight have attained escalating significance.…”
Section: Introductionmentioning
confidence: 99%
“…This indicator is a simple and effective spectral data processing method that combines some characteristic bands in a certain mathematical form. This method greatly eliminates the redundancy of hyperspectral data; requires less computation; and is widely used to estimate changes in crop yield [10], pigment content [24], canopy structure [25], and water status [26]. Several previous studies have constructed spectral indices for identifying and detecting crop diseases for disease detection using sensitive bands for a particular disease.…”
Section: Introductionmentioning
confidence: 99%